Pendugaan komponen varians dan kovarians genetik beberapa komponen hasil padi pada generasi f4 dan f5=Estimation of Genetic Variance-Covariance of F4 and for Several Yield Components in Rice - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1997)
.The aims of this study were (1) to estimate genetic variance-covariance for rice yield components of several lineages in F4 and F5 generation of selfing, and (2) to partition them into additive, dominance, and epistatic components. Two rice parental lines (533 and SLPK), and their F4 and F5 progenies were used in this study based on two biallelic locus model. The F4 seed were planted on July 1995. Four plants were randomly harvested from each 66 F4 entries to generate 264 number F in February 1996. Four yield components, i.e. (1) 1000-seed weight, (2) total spikelet number per panicle, (3) unfilled spikelet number per panicle, and (4) productive tiller number were recorded. The data for each generation were subjected to analysis of variance to estimate genetic variance-covariance which were then partitioned into additive, dominance, and epistatic variance. Genetic variance for all of the traits tends to be lower in F, generation, except for total spikelet number per panicle between F, families which descending from a single F3 plant (V2Fi) and productive tiller number within F5 families with common F. parent (V3F). Negative estimates of genetic covariance, W2v4â were obtained fo 1000-seed weight, total spikelet number per panicle